Spatial Mapping Analysis and Determinants of Poverty Gap in Regencies/Cities on Java Island in 2024 - Windrie Estu Sayekti; Arivina Ratih Yulihar Taher (CV. ITTC INDONESIA, 2025)
The Poverty Gap Index (P1) is an important indicator for assessing the vulnerability of the poor, but it has received little attention in policy formulation. Java Island, as the national economic center, still shows significant disparities in welfare between regions. This study analyzes the spatial patterns and factors that influence P1 in 119 districts/cities on Java Island in 2024 by incorporating spatial dependence into the model. The methods used include Moran’s I, Local Indicators of Spatial Association (LISA), and Spatial Autoregressive Model (SAR). The results show significant clusters, where regions with high P1 are concentrated in rural areas in Central Java and East Java. GRDP per capita has a negative and significant effect on P1, while the number of social assistance beneficiaries has a positive and significant effect. Expected years of schooling had a negative but insignificant effect. The significant spatial coefficient (ρ) indicates that there are inter- regional influences that need to be taken into account in understanding the dynamics of poverty gap. These findings suggest that policies need to be designed with spatial dimensions in mind to strengthen the effectiveness of poverty alleviation.